The analysis and reconciliation of students' rebuttals in argumentation activities. Issue 1 (2nd January 2016) - Lin, Yu-Ren; Hung, Jeng-Fung
ABSTRACT: The present study investigated the guidance provided by science teachers to resolve conflicts during socioscientific issue-based argumentation activities. A graphical representation (GR) was developed as a tool to code and analyze the dialogue interaction process. Through the GR and qualitative analysis, we identified three types of dialogue reconciling strategies. The first one consists of teacher management, in which the teacher temporarily maintains the right to speak when students get mired in an emotional rebuttal situation. The second strategy involves the use of qualifiers to identify the strengths and weaknesses of an opposing argument. The third strategy consists of providing students with guidance to keep both parties (i.e. the students taking, respectively, the affirmative and negative positions) on the same discussion topic and can be used to assist teachers with forming broad questions that prompt students to conduct deeper discussions. These reconciling strategies were beneficial in that they helped students to argue in a more reflective way.